The use of Stilbestrol and Synovex implants for steers during the wintering and fattening period. - Koch, B.A.; Smith, E.F.; Cox, R.F.; Richardson, D.; Walker, G.L. (Kansas Agricultural Experiment Station, 2011)
The steers used in this study were implanted with either stilbestrol or Synovex at the start of the wintering period. The results of the first 112 days of the wintering period were reported in Circular 349. This report summarizes the results of the entire wintering period and also the results of the fattening period which followed.
Keywords: Beef; Stilbestrol; Synovex; Gain